Proteomic identification of a marker signature for MAPKi resistance in melanoma. (26th June 2019) - Paulitschke, Verena; Eichhoff, Ossia; Gerner, Christopher; Paulitschke, Philipp; Bileck, Andrea; Mohr, Thomas; Cheng, Phil F; Leitner, Alexander; Guenova, Emmanuella; Saulite, Ieva; Freiberger, Sandra N; Irmisch, Anja; et al.
Abstract: MAPK inhibitors (MAPKi) show outstanding clinical response rates in melanoma patients harbouring BRAF mutations, but resistance is common. The ability of melanoma cells to switch from melanocytic to mesenchymal phenotypes appears to be associated with therapeutic resistance. High‐throughput, subcellular proteome analyses and RNAseq on two panels of primary melanoma cells that were either sensitive or resistant to MAPKi revealed that only 15 proteins were sufficient to distinguish between these phenotypes. The two proteins with the highest discriminatory power were PTRF and IGFBP7, which were both highly upregulated in the mesenchymal‐resistant cells. Proteomic analysis of CRISPR/Cas‐derived PTRF knockouts revealed targets involved in lysosomal activation, endocytosis, pH regulation, EMT, TGFβ signalling and cell migration and adhesion, as well as a significantly reduced invasive index and ability to form spheres in 3D culture. Overexpression of PTRF led to MAPKi resistance, increased cell adhesion and sphere formation. In addition, immunohistochemistry of patient samples showed that PTRF expression levels were a significant biomarker of poor progression‐free survival, and IGFBP7 levels in patient sera were shown to be higher after relapse. Synopsis: Therapy resistance towards BRAF inhibition and relapse in skin cancer are frequently associated with cellular phenotype switching, but the molecular control of this plasticity and discriminating markers remain unclear. Multidimensional expression profiling of resistant and sensitive primary melanoma reveals functional biomarkers and potential targets associated with poor progression‐free survival. Combined proteome and transcriptome analyses identify a core set of 15 MAPKi resistance‐associated proteins. PTRF and IGFBP7 are upregulated in resistant mesenchymal‐type melanoma cells. Depletion of PTRF results in downregulation of lysosomal endocytosis targets and EMT signaling. Overexpression of PTRF induces MAPKi‐resistance, increased cell adhesion and sphere formation. PTRF expression correlates with poor progression‐free survival under MAPKi treatment. Abstract : Comparative proteome and transcriptome profiling of primary skin cancers identifies biomarkers associated with therapy resistance and relapse.